Para Além do Conceito Cotidiano: a concepção de atividades de ensino-aprendizagem com vistas à (re)conceitualização de apresentações acadêmicas - Dellagnelo, Adriana de Carvalho Kuerten; Silva, Leonardo da; Rocha, Nara Vieira da (BELT - Brazilian English Language Teaching Journal, 2016)
Este estudo investiga a concepção de atividades de ensino-aprendizagem de dois professores para um curso de inglês com foco em apresentações acadêmicas oferecidas pelo programa “Idiomas sem Fronteiras”. Em particular, procura-se desvendar até que ponto tal concepção abriu o caminho para a (re)conceptualização de apresentações acadêmicas ao longo do curso. Apresenta-se a noção vygotskyana de desenvolvimento de conceitos para entender a relação entre conceitos espontâneos e científicos na narração dos professores sobre a sua prática. Essas narrativas sugerem que os professores em questão parecem preocupados com a subjetividade dos alunos bem como com a importância de conceitos cotidianos na construção do conceito científico nas apresentações acadêmicas. Nesse sentido, apesar do fato dos próprios professores não fazerem referência explícita ao desenvolvimento de conceitos, a sua prática pedagógica se organiza para promover a (re)conceptualização de apresentações acadêmicas pelos alunos através do confronto de conceitos espontâneos e científicos. ************************************************************************************************************************************************************************************************************ Beyond the Everyday Concept: the conception of teaching-learning activities aimed at the (re)conceptualization of academic presentations This study investigates two teachers’ conception of teaching and learning activities for an English course focusing on academic presentations offered by the “Languages Without Borders” program. Particularly, the aim is to unveil to what extent such conception has opened room for the (re)conceptualization of academic presentations along the course. Vygotsky’s notion of concept development is presented so as to understand the relation between spontaneous and scientific concepts in the teachers’ narration of their practice. These narratives suggest that the teachers in question seem concerned with the students’ subjectivity as well as with the importance of everyday concepts in the construction of the scientific concept of academic presentations. In this sense, despite the fact that the teachers themselves do not make explicit references to concept development, their pedagogical practice is organized so as to promote the students’ (re)conceptualization of academic presentations through the confrontation of spontaneous and scientific concepts. Keywords: Concept development; Spontaneous concepts; Scientific concepts; Academic presentations.